Revision of the species-group of Mischocyttarus (Omega) filiformis (de Saussure 1854), with description of three new species (Hymenoptera, Vespidae) - Borges, Rafael Cabral; Silveira, Orlando Tobias (Zootaxa, 2019)
A taxonomic revision of the species-group related to M. filiformis (Saussure 1854) is presented along with an identification key to species. After Richards (1978) and following the rearrangement of the subgenus Omega de Saussure by Silveira (2008), the species-group considered herein included three species in addition to M. filiformis; i.e. M. buyssoni (Ducke 1906), M. napoensis Richards 1978 and M. omicron Richards 1978. In the present work, three new species are added: M. nazgul sp. nov.; M. asahi sp. nov.; M. kallindusfloren sp. nov.; the male of M. filiformis is also described here in detail for the first time, and new distributional records are provided for the included species.